2005
DOI: 10.1007/s00431-005-1725-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of hyperviscosity and subclinical atherosclerosis in obese schoolchildren

Abstract: Hyperviscosity is related to subclinical atherosclerosis in obese schoolchildren. Viscosity parameters contribute new information in addition to body mass index, blood pressure and blood lipids and may help to facilitate risk stratification in obese paediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The aim of the present study was to compare EA in a group of obese patients without type 2 diabetes, arterial hypertension, or dyslipidemia and in a control group and to determine whether this rheological parameter shows significant changes with weight loss obtained with diet treatment. Like us, most authors have found higher values of EA indices in obese patients compared with a control group (2, 3, 4, 5, 6, 7, 8), using a Myrenne aggregometer, one of the most commonly used in clinical hemorheology laboratories because of its easy handling and reproducibility (17). EA has not only been evaluated in the present study with a Myrenne aggregometer but also with a Sefam aggregometer, which supplies additional information on the EA process, assessing the extent of aggregates, Ta and γD, i.e., the shear rate required to disaggregate the rouleaux.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The aim of the present study was to compare EA in a group of obese patients without type 2 diabetes, arterial hypertension, or dyslipidemia and in a control group and to determine whether this rheological parameter shows significant changes with weight loss obtained with diet treatment. Like us, most authors have found higher values of EA indices in obese patients compared with a control group (2, 3, 4, 5, 6, 7, 8), using a Myrenne aggregometer, one of the most commonly used in clinical hemorheology laboratories because of its easy handling and reproducibility (17). EA has not only been evaluated in the present study with a Myrenne aggregometer but also with a Sefam aggregometer, which supplies additional information on the EA process, assessing the extent of aggregates, Ta and γD, i.e., the shear rate required to disaggregate the rouleaux.…”
Section: Discussionmentioning
confidence: 86%
“…Alterations in the hemorheological profile in obese patients may promote, in addition to other mechanisms, the development of atherothrombotic and thromboembolic events. In this setting, among the hemorheological factors, erythrocyte aggregation (EA) 1 has been reported to show the most contradictory results (2, 3, 4, 5, 6, 7, 8). The studies performed in obese patients have evaluated aggregation index (IA), and only two of them have determined the ability of erythrocyte rouleaux to be dissociated into individual red blood cells by means of the total disaggregation threshold (γD) needed for erythrocytes to disaggregate (6, 9), which is an important contribution to the knowledge of rouleaux characteristics, and, therefore, of its ability to promote thrombus formation.…”
Section: Introductionmentioning
confidence: 99%
“…Results from this study cohort linking intima-media thickening and endothelial dysfunction to childhood obesity and to hyperviscosity have been reported before [31,32]. We defined obesity as having a body weight above the 95% percentile on age-specific and gender-specific Chinese growth charts.…”
Section: Subjectsmentioning
confidence: 92%
“…Although we did not measure blood viscosity in this study, it is well known that viscosity is increased in animals fed with an atherogenic diet [35] and in hypercholesterolemic patients [36]. The increase in blood viscosity previously reported varies from 0.8% to 8.2% [37], [38], [39]. In hemodynamic studies of early atherosclerotic changes [26], vascular resistance was found to be increased in the resting state and also during maximal vasodilation.…”
Section: Discussionmentioning
confidence: 69%